THU0367 Identification of Differentially Methylated Genes in Purified Disease-Relevant Blood Cell Populations in Patients with Spondyloarthritis. (15th July 2016) - Tost, J.; Bugge Tinggaard, A.; Wang-Renault, S.-F.; Busato, F.; Dougados, M.; Miceli-Richard, C.
Abstract : Background: Spondyloarthritis (SpA) is a complex disease involving genetic, epigenetic and environmental contributions to disease risk. However, associated polymorphisms explain only 25% of SpA heritability suggesting that a significant inherited component of SpA is not being detected by screening genetic polymorphisms and suggests an important role for epigenetic factors such as DNA methylation. However, no comprehensive analysis of genome-wide DNA methylation in disease relevant blood cell populations has so far been performed in SpA allowing to experimentally verify this hypothesis. Objectives: This study aimed to perform a genome-wide DNA methylation analysis in sorted CD4 and monocytes from SpA patients compared with controls. Methods: In the exploratory cohort, 24 SpA patients and 16 age and sex-matched controls were analyzed. SpA patients were monocentrically recruited between October 2014 and May 2015 in the department of rheumatology (Cochin hospital). These patients had an active disease despite NSAIDs intake and were eligible for a TNF-blocker treatment. The mean BASDAI (± SD) was 53.2±23.7; ASDAS 3.2±1.1 and CRP 13±16.6. Among these patients, 23 fulfilled the ASAS classification criteria (imaging arm) with sacro-iliitis on X-rays (n=16) or objective signs of inflammation on MRI (n=21). Only one patient fulfilled the clinical arm. Genome-wide DNA methylation patterns were analyzed in cell-sorted (MACS) monocytes and CD4 T-lymphocyte populations from SpA patients and controls using the Illumina 450K Infinium Human Methylation 450K BeadChip allowing the simultaneous quantitative monitoring of more than 480, 000 CpG positions. Results: In CD4 cells 122 CpGs in 82 promoter regions of genes were found to be differentially methylated using stringent quality thresholds including several genes involved in disease-relevant signaling cascades such as Wnt-signaling and genes in which genetic polymorphisms have previously been associated with susceptibility to SpA. With 158 CpGs located in 86 promoter regions, slightly more genes were found to be differentially methylated in monocytes. Differentially methylated loci included again genes in Wnt signaling and bone metabolism, osteoblast or chondrocyte-specific genes as well as genes that have previously been shown to be implicated in related diseases such as psoriasis. A single gene was found differentially methylated in both monocytes and T-lymphocytes underlining the importance to perform these epigenetic analyses in purified cell populations. Validation of these differentially methylated positions in 12 genes at single-nucleotide resolution is ongoing in monocytes and CD4 lymphocytes from 12 additional patients and 12 additional controls using the highly quantitative pyrosequencing technology. Conclusions: This study is the first to analyze genome-wide DNA methylation in purified disease-relevant blood cell populations in SpA bringing into evidence a moderate number of promoters whose deregulation might contribute to the pathogenesis of SpA. Integration with RNA expression data will allow defining the functional impact of the DNA methylation patterns to better understand the molecular changes in SpA and potentially identify novel targets for therapeutic intervention. Disclosure of Interest: None declared